T cells distinguish MHC-peptide complexes formed in separate vesicles and edited by H2-DM. - Pu, Z; Lovitch, S; Bikoff, E; Unanue, E (2004)
The peptide spanning residues 48-61 of hen egg white lysozyme (HEL) presented by I-A(k) gives rise to two T cell populations, referred to as type A and B, that distinguish the complex generated intracellularly upon processing of HEL from that formed with exogenous peptide. Here, we ascribe this difference to recognition of distinct conformers of the complex and show that formation of the two complexes results from antigen processing in different intracellular compartments and is dependent upon H2-DM. While the type A complex preferentially formed in a lysosome-like late vesicle, the type B complex failed to form in this compartment; this distinction was abolished in antigen-presenting cells lacking DM. Experiments in vitro indicated that H2-DM acts directly on the complex to eliminate the type B conformation. We conclude that different antigen-processing pathways generate distinct MHC-peptide conformers, priming T cells with distinct specificity that may play unique roles in immunity.